Kondisi Sosial Rakyat Suriah Pasca Revolusi 2011 Dalam Novel Ayyām Fī Bābā ‘Amrū Karya Abdullah Maksūr: Analisis Sosiologi Sastra - Istiqomah, Nurul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Ayyām fī Bābā 'Amrū novel by Abdullah Maksūr is one of novels that came out after the Arab Spring that hit Syria. The revolution in Syria occurred because of the people's desire to overthrow al-Assad regime which had been in power for decades. Demonstrations in Syria then ended into a civil war that never ended until now. This novel takes the story of the condition of Syrian society after the Syrian revolution erupted in 2011 and describes the conflict between the military and the Syrian people. This study aims to reveal the social conditions experienced by Syrians of the Syrian revolution based on data in the Ayyām fī Bābā 'Amrū novel, the social reality of Syrian society, and the relationship between the structure of the text and the social reality of Syrian society. The theory used in this study is Alan Swingewood's the sociology of literature theory with the concept that literary work is a mirror of the age. The method used is the literary of sociology method which is a moving method of literary data. The results of this study indicate that there are several causes of the Syrian revolution mentioned in the novel, such as the desire to be free from a regime that has been in power for decades, corruptions, inspired by other Arab countries, and a long-held hatred. The social conditions experienced by the Syrian people during the revolution were experiencing intimidation from the military, the people were arrested without any fault, some Syrians were tortured in military prisons, shootings, bombings and chaos in several cities, some girls experienced sexual harassment, the people were divided between supporting the regime or opposition, and most Syrians flee to neighboring countries. The social condition that occurs in the novel is a representation of the social reality that occurred in Syrian society after the revolution in 2011.